Adoção Intuitu Personae - Kusano, Suely Mitie (2006)
The theme of this doctorate thesis is the intuitu personae adoption , considering the present relevance of the subject, the attendance to the minor s major interests in his insertion into the familiar life and the difficulties faced by those who show disposition to adopt children, taking as basis the legal rules expressed by the Child and Adolescent Statute. For this, and having analyzed the brazilian legal specific dispositions, we researched the practical problems observed in the accomplishment of the intention when the biological parents indicate the adopting person, concomitantly with their manifestation of giving the son to adoption, also confronting with the orientations internationally consigned in the Haia Convention to attend the minor, the family and the society s interests, as well as the major dispositions of the national doctrine and jurisprudence. By means of a retrospect of the historical evolution of the adoption institute, of a study of how the adoption is practiced nowadays in some outstanding countries, of a comparison with similar legal institutes and also of sociological and medical indications, we can sustain the viability of the intuitu personae adoption as a further way and process of minors adoption in Brazil. We think this can make the adoption process quicker, can support the minors interests and, at the same time, can shorten the social impact caused by the immense number of minors waiting for a definitive familiar life